Healthy Eating: Change Up Your Breakfast! - Emily Minton (EDIS, 2012)
Are you tired of eating the same breakfast every day? Try a few of these ideas and maybe you’ll find a new favorite! This 2-page fact sheet was written by Emily Minton and published by the UF Department of Family, Youth and Community Sciences, March 2012.